An ex vivo co‐culture model system to evaluate stromal–epithelial interactions in breast cancer. Issue 2 (26th June 2012) - Salameh, T.S.; Le, T.T.; Nichols, M.B.; Bauer, E.; Cheng, J.; Camarillo, I.G.
Abstract Breast cancer is the most commonly diagnosed cancer among women worldwide. High breast cancer incidence and mortality rates, especially in obese patients, emphasize the need for a better biological understanding of this disease. Previous studies provide substantial evidence for a vital role of the local extracellular environment in multiple steps of tumor progression, including proliferation and invasion. Current evidence supports the role of adipocytes as an endocrine organ, which produces steroid hormones, pro‐inflammatory cytokines and adipokines, such as leptin. To further define the role of the mammary microenvironment on tumorigenesis, we have developed an adipose‐tumor epithelial cell co‐culture system designed to reproduce the in vivo mammary environment. We validate this model through use of coherent anti‐Stokes Raman scattering (CARS) microscopy, a label‐free vibrational imaging technique. CARS analysis demonstrates the sustained viability of the adipocytes, and that mammary cancer cell morphology parallels that of tumors in vivo. Also, characterized was the influence of mammary adipose tissue on tumor cell growth and migration. Adipose tissue co‐cultured with mammary tumor epithelial cells, in the absence of any serum or supplemental growth factors, resulted in substantial increases in growth and migration of tumor cells. In conclusion, this novel co‐culture system provides an ideal model to study epithelial–stromal interactions in the mammary gland. Understanding the relationship between adipose tissue, the most abundant and least studied component of the breast stroma and tumor epithelial cells is critical to clarifying the influence of obesity on the development, progression and prognosis of breast cancer.